2001
DOI: 10.1111/0885-9507.00241
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Optimization Using Cellular Automata with Application to the Combined Trip Distribution and Assignment System Optimal Problem

Abstract: In this paper, meta-optimization and cellular automata have been introduced as a modeling environment for solving large-scale and complex transportation problems. A constrained system optimum combined trip distribution and assignment problem was selected to demonstrate the applicability of the cellular automata approach over classical mixed integer formulation. A mathematical formulation for the selected problem has been developed and a methodology for applying cellular automata has been presented. A numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The CA model is favoured by many scholars [37][38][39][40][41] for traffic simulation due to its simple rules and high efficiency.…”
Section: Micro-simulation Based On Cellular Automatamentioning
confidence: 99%
“…The CA model is favoured by many scholars [37][38][39][40][41] for traffic simulation due to its simple rules and high efficiency.…”
Section: Micro-simulation Based On Cellular Automatamentioning
confidence: 99%
“…Recently, some research showed that CA can be used as a practical and efficient optimization engine, which relies on the key properties of: locality of the neighborhoods interactions, homogeneity of the evolving mechanism, parallelism of the computation, and simplicity of the model structure. CA has been extensively used as a viable and efficient optimization algorithm for the structural design (Kita & Toyoda, 2000, Missoum, Gürdal, & Setoodeh, 2005, and Setoodeh, Gürdalb, & Watson, 2006, estimating shortest path (Adamatzky 1996) or trip distribution problems (El Dessouki, Fathi, & Rouphail, 2001), and computer networks (Shuai & Zhao, 2004).…”
Section: Cellular Automatamentioning
confidence: 99%